The determinant factors of continuance intention to revisit omnichannel retailer companies: mean-end chain theory approach - Arta Moro Sundjaja; Prio Utomo; Darrell Matthew; Garry Reverio Hellianto; Niko Sutanto Putra (Cogent Business & Management, 2024)
The purpose of the study was to examine the determinant factors that influence the intention to revisit retailer omnichannel in Indonesia with Mean-End Chain Approach. The internet economy growth drives the use of the omnichannel strategy in Indonesia retail companies. The past research showed that there was inconsistency in the understanding of omnichannel strategy channel integration. The Means-End Chain Theory believes can help to enlighten this integration by understanding the attribute, consequences, and values of customer omnichannel strategy acceptances. The research is cross-sectional quantitative research with sample of 248 respondents that gathered using convenience sampling. The Disjoint Two-Stage Approach Partial Least Square Structural Equation Model (PLS-SEM) was used to analyse the high order construct model. The finding shows that both customer satisfaction and shopping value were the mediating variables between channel integration and intention to revisit. The integrated order fulfilment, integrated transaction information, integrated customer service, and integrated customer service influenced channel integration were identified as the dominant dimensions to the channel integration. The managerial implication emphasized on the various channel integration optimization and integration during pre and post customer shopping journey. This study enriches the customer behavior studies, especially in the importance of channel integration with Mean-End Chain Theory approach.
Keywords: 650; intention to revisit; means-end chain theory; shopping value; channel integration; omnichannel; retail company